Transformational Leadership dan Readiness to Change: Model Mediasi dengan Proactive Personality - Diva Marsheilla Zaura; Missiliana Riasnugrahani (Universitas Trunojoyo Madura, 2023)
Changes in the organization are something that happens frequently. Therefore, the readiness of employees to face change is an important thing that needs to be developed by leaders. This study aims to determine the mediating role of proactive personality in the relationship between transformational leadership and readiness to change among employees. Through a convenience sampling technique, we have 45 employees from division who were making changes in their management operations as respondents. Data collection techniques used the Multifactor Leadership Questionnaire (MLQ), Readiness for Change Questionnaire-II (RFCQ-II), and Proactive Personality Scale questionnaires. The three instruments have a good validity value, which ranges from 0.3 to 0.7, and are reliable with a reliability value above 0.7. Through regression analysis techniques, especially the 4 Hayes PROCESS mediation model, we find that proactive personality fully mediated the relationship between transformational leadership and readiness to change (β = 0.37, [0.21; 0.56]). This study indicates that leaders who provide opportunities for their subordinates to express ideas and solve problems in their work and create opportunities for their followers to participate in decision-making can increase the change readiness of their employees only if the subordinates have a proactive personality. Employees with proactive personalities can identify opportunities, take the initiative, survive, and are not afraid of changes around them, so they are better prepared to change.